Circulating MicroRNAs as Cancer Biomarkers: Can They Play a Role in Clinical Practice? Short Review - Angelo Michele Carella; Teresa Marinelli; Armando Mel fi tano; Michele Di Pumpo; Giovanni Modola; Matteo Conte; Angelo Benvenuto (Archives of Preventive Medicine - Peertechz Publications, 2016)
microRNAs (miRNAs) are a large family of short noncoding RNA sequences which modulate gene expression and regulate a wide range of biological processes. There is evidence that miRNAs may have a role in molecular mechanisms linked to tumorigenesis and a lot of studies have proven that some miRNAs are closely correlated with cancer. miRNAs are not only contained in tissue cells but they are also detectable in extracellular sites, as plasma, urine, cerebrospinal and other body fluids where they are remarkably stable, so that may be identified and measured. Since tumors alter the normal concentrations of circulating miRNAs, these oligo nucleotides can be used as cancer biomarkers. Circulating miRNAs detection may be used for early diagnosis, staging, follow up, assessment of therapeutic responses and therapy outcomes in several types of human cancer as colorectal cancer, pancreatic adenocarcinoma, lung cancer and malignant pleural mesothelioma, urinary and prostate cancer, breast cancer, hematologic malignancies, glioblastoma and others. Quantitative real-time Polimerase Chain Reaction (qRT-PCR) is one of the most sensitive techniques for quantifying circulating miRNAs. Deep sequencing technology has recently emerged as an attractive approach for miRNA analysis; in some cases this technique showed  more specificity and sensitivity compared to qRT-PCR and Microarray, also allowing identifi cation of novel MiRNA isoforms. Given that current serological cancer biomarkers, commonly employed in follow up, have low specificity and sensitivity, it is plausible that circulating miRNA detection can be included in futureroutine clinical examinations for management of cancer patients, although costs and wide availability of quantifying techniques could represent a critic limit. Further comparative studies will be required.